Exogenous Addition of 25‐Hydroxycholesterol Reduces Level of Very Long‐Chain Fatty Acids in X‐Linked Adrenoleukodystrophy. Issue 2 (11th February 2019) - Jang, Jiho; Lee, Jung Wuk; Song, Jiho; Kim, Dong‐Wook; Min, Kyung Hoon
Abstract: X‐Linked adrenoleukodystrophy (X‐ALD) is a severe metabolic disorder characterized by the accumulation of very long‐chain fatty acids (VLCFAs). Recently, we demonstrated that levels of 25‐hydroxycholesterol (25‐HC) and cholesterol 25‐hydroxylase ( CH25H ) were found to be elevated in X‐ALD. Herein, we report that the exogenous addition of 25‐HC significantly reduces C26:0 levels in X‐ALD patient‐derived fibroblasts and oligodendrocytes differentiated from induced pluripotent stem cells (iPSCs) derived from X‐ALD patients. Moreover, 25‐HC treatment was found to down‐regulate the expression of ELOVL1, a key enzyme for the synthesis of C26. In addition, activation of liver X receptor (LXR), a molecular target of endogenous 25‐HC, also reduced C26:0 level. The reduction of C26:0 levels by 25‐HC treatment might result, at least partially, from the decrease of ELOVL1 expression as well as the activation of LXR. Our findings could provide a better understanding of the role of 25‐HC in X‐ALD and useful information to find therapeutic agents to treat X‐ALD. Abstract : Time for expression : 25‐Hydroxycholesterol treatment significantly reduces the levels of very long‐chain fatty acids (C26:0) in X‐linked adrenoleukodystrophy fibroblasts, which may result partially from the decrease of ELOVL1 expression as well as activation of liver X receptor.